Current voltage characteristics of a carbon nanotube field effect transisitor - 253894 Mohammad Taghi Ahmadi; Mohammad Taghi Ahmadi, author; Javad Karamdel, author; Razali Ismail, author; C.F. Dee, author; Burhanuddin Yeop Majlis, editor; IEEE International Conference on Semiconductor Electronics (2008: Johor Bahru) (Skudai : Universiti Teknologi Malaysia, 2008)
PRZSL